FrAngel: component-based synthesis with control structures - Shi, Kensen; Steinhardt, Jacob; Liang, Percy (Proceedings of ACM on programming languages, 2019)
In component-based program synthesis, the synthesizer generates a program given a library of components (functions). Existing component-based synthesizers have difficulty synthesizing loops and other control structures, and they often require formal specifications of the components, which can be expensive to generate. We present FrAngel, a new approach to component-based synthesis that can synthesize short Java functions with control structures when given a desired signature, a set of input-output examples, and a collection of libraries (without formal specifications). FrAngel aims to discover programs with many distinct behaviors by combining two main ideas. First, it mines code fragments from partially-successful programs that only pass some of the examples. These extracted fragments are often useful for synthesis due to a property that we call special-case similarity. Second, FrAngel uses angelic conditions as placeholders for control structure conditions and optimistically evaluates the resulting program sketches. Angelic conditions decompose the synthesis process: FrAngel first finds promising partial programs and later fills in their missing conditions. We demonstrate that FrAngel can synthesize a variety of interesting programs with combinations of control structures within seconds, significantly outperforming prior state-of-the-art.